Research on the use of various pool water cleaning assist devices solutions in indoor swimming pools - Piechurski, Florian (Instal, 2019)
The results of pool water testing for various treatment methods show that the use of traction treatment support methods for ozonation or irradiation processes in UV reactors or a combination of these processes in one device allow maintaining water quality in accordance with the applicable RMZ dated November 9, 2015. It seems that maintained water quality is crucial, i.e. maintaining bound chlorine level below 0.3 mg Cl2/dm3.
Keywords: pool water treatment; bounded chlorine; ozonation; irradiation processes in UV reactors; results